2014
DOI: 10.1002/nbm.3159
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric MRI characterization of healthy human thigh muscles at 3.0 T - relaxation, magnetization transfer, fat/water, and diffusion tensor imaging

Abstract: Muscle diseases commonly have clinical presentations of inflammation, fat infiltration, fibrosis, and atrophy. However, the results of existing laboratory tests and clinical presentations are not well correlated. Advanced quantitative MRI techniques may allow the assessment of myo-pathological changes in a sensitive and objective manner. To progress towards this goal, an array of quantitative MRI protocols was implemented for human thigh muscles, their reproducibility was assessed, and the statistical relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 74 publications
10
74
0
2
Order By: Relevance
“…As noted previously (15), voluntary and involuntary motion artifacts can occur during data collection (~10 min for a full dataset). These movements can result from gross subject movements, prolonged muscle contraction, and/or brief twitches.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…As noted previously (15), voluntary and involuntary motion artifacts can occur during data collection (~10 min for a full dataset). These movements can result from gross subject movements, prolonged muscle contraction, and/or brief twitches.…”
Section: Introductionmentioning
confidence: 83%
“…For example, the PSR is correlated with myelin content in white matter (9,12). QMT studies have also been performed in healthy skeletal muscles (13-15) and in a murine model of inflammation (16). It was demonstrated that PSR may also serve as a biomarker of inflammation (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Недавно при применении уско-ренных последовательностей с оптимизированными схемами насыщения были получены обнадеживающие результаты с высокой корреляцией различий магнити-зации с фиброзом в печени [102]. Перенос магнитиза-ции имеет высокий уровень в скелетных мышцах, его происхождение и механизмы развития были изучены несколькими группами ученых у здоровых людей, а также при старении и заболеваниях мышц, однако связь изменений с фиброзом по-прежнему остается до конца не ясной [103][104][105][106][107][108]. Много вопросов вызвало обнаружение обратной корреляции различий магни-тизации с возрастными изменениями у здоровых лю-дей.…”
Section: лекции и обзорыunclassified
“…Cette méthode a été transférée chez l'homme sous le nom d'ISIS-CPMG. Elle a permis d'identifier des composantes T2 intra-et extracellulaires mais n'a jusqu'à présent pas mis en évidence cette composante de spins à T2 très court (Schwenzer et al 2009a ;Sinclair et al 2010 ;Sinclair et al 2012 ;Morrow et al 2014 ;Li et al 2014 ;Li et al 2015). La corrélation négative entre le contraste de transfert d'aimantation et l'âge dans une cohorte d'individus sains est par exemple, relativement déroutante .…”
Section: Outils D'évaluation Par Imagerie Rmn Actuellement En Cours Dunclassified